Níveis séricos de interleucina-6 e polimorfismo - 174G>C em infecção latente pelo Mycobacterium tuberculosis - Lopes, Fernando Henrique Azevedo (2012)
Interleukin-6 (IL-6) is an important cytokine involved in the pathogenesis of multiple infectious diseases. The aim of this study was to investigate the levels of IL-6 production and to correlate to the -174G>C polymorphism at the IL-6 gene in latent infection with M. tuberculosis (ILTB). As controls, two groups were used. One of them with active pulmonary tuberculosis (TB) patients and the other with healthy blood donors. ILTB group was composed by 15 individuals, selected among active pulmonary TB contacts seen at the Hospital São José de Doenças Infecciosas and the Centro de Saúde da Família Anastácio Magalhães. TB group had 38 patients with active pulmonary disease seen at the Hospital de Messejana, Hospital de Maracanaú and the Hospital Geral Dr. César Cals. The third group was composed by 63 healthy blood donors from the Centro de Hematologia e Hemoterapia do Ceará. Serum levels of IL-6 were measured by an ELISA using specific kits from Invitrogen Corporation. For DNA purification a GFX Genomic Blood DNA Purification kit (GE Healthcare) was used. The -174GC polymorphism was analyzed by a SSP-PCR method using One-Lambda kits. Median values of serum levels of IL-6 from ILTB, TB and healthy groups were, respectively, 1.7 pg/mL, 4.3 pg/mL and 0.5 pg/mL (p < 0.0001). For the three studied group, the most frequent genotype found was the G/G (ILTB = 80%; TB = 58.9%; saudáveis = 62.8%). In conclusion, it is possible to consider that IL-6 should play an important role in the maintenance of latent infection state as its concentrations were 3.4 fold higher in ILTB group than that of healthy controls. Moreover, the -174GC polymorpism was not functional in the ILTB group.